1991
DOI: 10.1111/j.1540-8159.1991.tb05083.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Infection with Mycobacterium Avium Complex

Abstract: A 21-year-old. HIV negative, malnourished, homeless woman with congenital heart block had a pacemaker implanted at 7 years of age and multiple procedures thereafter. The most recent of these procedures was replacement of a pulse generator in the right pectoral region. Four months later she had fever, pain, and swelling over the implant site resulting from infection with mixed flora and Mycobacterium avium complex. The pacemaker system was removed by thoracotomy via a median sternotomy and a new DDD pacemaker s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Corynebacterium species, Propionibacterium acnes, Gram-negative bacilli 37,38 including Pseudomonas aeruginosa, 43 and Candida species account for a minority of CIED infections. Fungi other than Candida 44 and nontuberculosis mycobacteria 45,46 are rarely identified as pathogens in CIED infection.…”
Section: Microbiologymentioning
confidence: 99%
“…Corynebacterium species, Propionibacterium acnes, Gram-negative bacilli 37,38 including Pseudomonas aeruginosa, 43 and Candida species account for a minority of CIED infections. Fungi other than Candida 44 and nontuberculosis mycobacteria 45,46 are rarely identified as pathogens in CIED infection.…”
Section: Microbiologymentioning
confidence: 99%
“…These represented either pacemaker generator site infection or epicardial lead infection without documented endocarditis. One report [3] described a pacemaker generator site infection with Mycobacterium avium complex that included only the subcutaneous part of the transvenous leads. Another report described a case of pacemaker pocket infection due to both Mycobac- terium chelonae and Mycobacterium fortuitum [4].…”
Section: Discussionmentioning
confidence: 98%
“…Review of literature showed 25 case reports of CIED related infections due to Mycobacterium species [17–39], with two different Mycobacteria species in one patient [20], and three cases in one report [31]. Tables 2 and 3 show Mycobacterial infections of implanted pacemakers and ICDs respectively, as reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…The infection occurred between 8 days and 20 years from the last device related procedure. It occurred with both transvenous [17, 18, 20–22, 2427, 30, 31, 33–39] and epicardial device implantations [19, 23, 28, 29, 32]. Mycobacterium tuberculosis was reported in seven cases [18, 23, 28, 31, 36] with mostly pocket infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation